2018
DOI: 10.1038/s41598-018-31615-y
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Inhibits Tumor Growth in Mice by Suppressing Pyruvate Kinase M2-mediated Aerobic Glycolysis

Abstract: Shift metabolism profile from mitochondrial oxidative phosphorylation to aerobic glycolysis (Warburg effect) is a key for tumor cell growth and metastasis. Therefore, suppressing the tumor aerobic glycolysis shows a great promise in anti-tumor therapy. In the present study, we study the role of shikonin, a naphthoquinone isolated from the traditional Chinese medicine Lithospermum, in inhibiting tumor aerobic glycolysis and thus tumor growth. We found that shikonin dose-dependently inhibited glucose uptake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 32 publications
3
79
1
Order By: Relevance
“…There are many small molecule inhibitors and hormones that inhibit cell proliferation by targeting PKM2 (77)(78)(79). The inhibitors, namely shikonin and its analogs, flavonoid derivatives, and 2,3-dithiocarbamate substituted naphthoquinones bind to the allosteric site of PKM2, which leads to reduced glycolysis in cancer cells (77,(80)(81)(82).…”
Section: Pkm2 As a Potential Target For Cancer Therapymentioning
confidence: 99%
“…There are many small molecule inhibitors and hormones that inhibit cell proliferation by targeting PKM2 (77)(78)(79). The inhibitors, namely shikonin and its analogs, flavonoid derivatives, and 2,3-dithiocarbamate substituted naphthoquinones bind to the allosteric site of PKM2, which leads to reduced glycolysis in cancer cells (77,(80)(81)(82).…”
Section: Pkm2 As a Potential Target For Cancer Therapymentioning
confidence: 99%
“…These data further clarified the anti-tumor activity of shikonin in cervical cancer. The doses used in this were based on other studies, 10,[48][49][50] which showed substantial inhibitory effects without noticeable toxicity. Our findings suggested that shikonin suppressed growth of human cervical cancer via regulating miR-183-5p/Snail/Vimentin/E-cadherin signaling regulatory axis.…”
Section: Dovepressmentioning
confidence: 99%
“…Several studies had shown that SK inhibits the growth of lung cancer cells and the glycolysis process of cervical cancer cells by inhibiting the expression of PKM2. 23,37 Therefore, we used q-PCR and Western blot to detect the expression of PKM2 after SK treatment. Our results demonstrated that of all glycolytic enzymes, expression of PKM2 protein and mRNA was reduced to the greatest extent with SK treatment in both LM3 and SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 99%